21st Century Skills: An Analysis of Educational Preparation in the United States and Indonesia in Creating an Educated Generation - Aprilia, Tria; Jeniah, Amin; Mutharom, Taufik (Literacy: Journal of Education and Social Science, 2023)
This research discusses the analysis of educational preparation in America and Indonesia in creating an educated generation that is ready to face the demands of the 21st century. The 21st century is marked as an era of openness and globalization which presents fundamental changes in human lifestyles. Education in the 21st century must be able to adapt to these changes and prepare an educated generation with critical thinking, communication, creativity and collaboration skills. Through cooperation between America and Indonesia, the development of flexible curricula, project-based learning, the use of technology in learning, and collaboration between teachers can improve the quality of education and prepare the younger generation to face global challenges. It is hoped that the results of this research can provide useful insights in the development of 21st century education in both countries.